Elevation of Inflammatory Cytokines and Proteins after Intra-Articular Ankle Fracture: A Cross-Sectional Study of 47 Ankle Fracture Patients - That Minh Pham; Lars Henrik Frich; Kate Lykke Lambertsen; Søren Overgaard; Hagen Schmal (Hindawi Limited, 2021)
Introduction. Intra-articular fractures are the leading etiology for posttraumatic osteoarthritis (PTOA) in the ankle. Elevation of proinflammatory cytokines following intra-articular fracture may lead to synovial catabolism and cartilage degradation. We aimed to compare cytokine levels in injured and healthy ankle joints, examine the longer-term cytokine levels in fractured ankles, and investigate the association between cytokine levels in fractured ankles and plasma. Materials and Methods. In this cross-sectional study, synovial fluid (SF) and plasma of forty-seven patients with acute intra-articular ankle fractures and eight patients undergoing implant removal were collected prior to surgery. We determined concentrations of sixteen inflammatory cytokines, two cartilage degradation proteins, and four metabolic proteins and compared the levels in acutely injured ankles with those of the healthy contralateral side or during metal removal. Cytokine levels in injured ankles were also compared to serum cytokine levels. Nonparametric Wilcoxon rank-sum and Spearman tests were used for statistical analysis, and a p value below 0.05 was considered significant. Results. Compared to the healthy ankles, the synovial fluid in ankles with acute intra-articular fracture had elevated levels of several proinflammatory cytokines and proteases (IL-1β, IL-2, IL-6, IL-8, IL-12p70, TNF, IFNγ, MMP-1, MMP-3, and MMP-9) and anti-inflammatory cytokines (IL-1RA, IL-4, IL-10, and IL-13). The levels of cartilage degradation products (ACG, CTX-2) and metabolic mediators (TGF-β1 and TGF-β2) were also significantly higher. Synovial concentrations of ACG, IL-12-p70, IFNγ, IL-4, and bFGF correlated with serum levels. While most of the examined synovial cytokines were unchanged after implant removal, IL-4 and IL-6 levels were upregulated. Conclusions. We show that an acute ankle fracture is followed by an inflammatory reaction and cartilage degeneration. These data contribute to the current understanding of the protein regulation behind the development of PTOA and is a further step towards supplementing the current surgical treatment. This cross-sectional study was "retrospectively registered" on the 31th October 2017 at ClinicalTrials.gov (NCT03769909). The registration was carried out after inclusion of the first patient and prior to finalization of patient recruitment and statistical analyses: https://clinicaltrials.gov/ct2/show/NCT03769909?term=NCT03769909&draw=2&rank=1.